A novel enhanced stability detection algorithm for ablation catheters: purpose and application in high-power short-duration ablation - Valeriano, Chiara; Berte, Benjamin; Klemm, Ofer; Sigal, Alona; Zaknoun, Eid; Buytaert, Dimitri; De Potter, Tom (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAssessing catheter stability during ablation procedures is crucial. The current stability algorithm relies on end-expiration reference frame (Gated), requiring a full respiratory cycle before lesion tagging. This poses challenges with high-power, short-duration (HPSD) radiofrequency ablation workflows. To overcome these limitations, a novel algorithm, called Stability+, has been developed. It provides real-time tracking and analysis of catheter motion throughout the entire respiratory cycle.ObjectiveThe aim of our study was to assess the performance of the new Stability + algorithm in HPSD ablations and to compare it with the current algorithm.MethodsData from a series of consecutive left atrial ablations employing the new Stability + algorithm were prospectively collected. A retrospective analysis was conducted to compare the two algorithms.ResultsA total of 1,056 applications were delivered, 123 (11.6%) using QMODE + (90 W, 3–4 s), and 933 (88.4%) using QMODE (50 W, ablation index guided 350/500). The number of unstable applications, outside the end-expiration phase, was detected with the Stability + for 9 positions (7.3%) using the QMODE+. Average time-to-tag appearance was 2.5 ± 1 s with the Stability + vs. 9 ± 1.1 s with the Gated algorithm. During QMODE ablation sessions, the Stability + algorithm prevented overshooting in 84% of the ablation positions. No steam pop or perforation occurred.ConclusionThe novel Stability + algorithm enhances lesion tracking for HPSD workflows like QMODE+/QMODE and holds the potential to improve stability detection across all radiofrequency ablation modes, marking a significant advancement in the field.